Studi Kuantitatif Perilaku Investasi Generasi Z di Jabodetabek Studi Kasus Cryptocurency - Akbar, Bintang Mukhammad Burhanudin (Valid: Jurnal Ilmiah, 2025)
The rapid advancement of digital technology has driven the emergence of cryptocurrency as an increasingly popular investment alternative, particularly among Generation Z, who have grown up in the digital era. Despite the significant growth in crypto investors, the behavior and factors influencing Generation Z's interest and investment decisions remain insufficiently understood. This study examines the influence of knowledge, risk perception, and social media on investment interest and the impact of interest on cryptocurrency investment decisions. Using a quantitative approach with an associative design, data were collected from 150 Generation Z respondents in the Greater Jakarta area (Jabodetabek) and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that knowledge has a significant positive effect on interest, while risk perception has a significant adverse effect. Social media, on the other hand, does not significantly influence investment interest. Interest is shown to have a significant positive impact on investment decisions. The developed model demonstrates good reliability and validity, with an R² value of 77.1% for investment decisions. Ultimately, Generation Z's investment behavior is shaped by financial literacy and risk perception rather than mere social media exposure, highlighting the importance of educational interventions and adaptive policies.